THE LIMITATIONS OF PROFIT GRAPHS, BREAKEVEN ANALYSIS, AND BUDGETS. - Raun, Donald L. (The Accounting Review, 1964)
Abstract A sound knowledge of cost-volume-profit behavior and cost interrelationships is essential to many business decisions. Information which is easily understood but may not represent reality can lead to costly errors in judgment in business decisions. The management accountant certainly has a responsibility to provide management with something more than simply data. He has a responsibility to provide analyzed data, or useful information, for specific purposes. Yet he has a grave responsibility to avoid employing oversimplified techniques, or partial analysis, which may be misused or misunderstood by management. This article serves four purposes. First, to present the application and limitations of the Scatter Graph and Least Squares methods of studying the cost-volume-profit relationships of a company. Second, to present the possible weaknesses or limitations of Break-even Analysis and Profit Graphs. Third, to review some of the major statistical techniques of evaluating the significance of relationships. Fourth, to present the application of Multiple Regression Analysis, with the aid of a computer, to determine the cost-volume-profit relationship.